Multiscale Modeling of Agglomerated Ceria Nanoparticles: Interface Stability and Oxygen Vacancy Formation - Kim, Byung-Hyun; Kullgren, Jolla; Wolf, Matthew J.; Hermansson, Kersti; Broqvist, Peter (Frontiers in Chemistry, 2019)
The interface formation and its effect on redox processes in agglomerated ceria nanoparticles (NPs) have been investigated using a multiscale simulation approach with standard density functional theory (DFT), the self-consistent-charge density functional tight binding (SCC-DFTB) method, and a DFT-parameterized reactive force-field (ReaxFF). In particular, we have modeled Ce40O80 NP pairs, using SCC-DFTB and DFT, and longer chains and networks formed by Ce40O80 or Ce132O264 NPs, using ReaxFF molecular dynamics simulations. We find that the most stable 111/111 interface structure is coherent whereas the stable 100/100 structures can be either coherent or incoherent. The formation of 111/111 interfaces is found to have only a very small effect on the oxygen vacancy formation energy, Evac. The opposite holds true for 100/100 interfaces, which exhibit significantly lower Evac values than the bare surfaces, despite the fact that the interface formation eliminates reactive 100 facets. Our results pave the way for an increased understanding of ceria NP agglomeration.